YouTube and You: Experiences of Self-awareness in the Context Collapse of the Recording Webcam - Wesch, Michael (My University, 2010)
New media not only introduce new ways for us to express ourselves, but also new forms of self-awareness—new ways to reflect on who we are and how we relate to others. This article analyzes the experiences of self-awareness generated by creating, viewing, and responding to deeply personal, unaddressed vlogs on YouTube. Using a symbolic interactionist framework, it is argued that the globally connected, recording webcam linking privatized spaces creates a context for sharing profound moments of self-refl ection and for creating connections that are experienced as profoundly deep yet remain ephemeral and loose.
Keywords: YouTube; New media; Goffman; Self-awareness; Webcam; Online video; Self; Anthropology; Ethnography